2020
DOI: 10.1063/5.0003095
|View full text |Cite
|
Sign up to set email alerts
|

Metalorganic chemical vapor phase deposition of AlScN/GaN heterostructures

Abstract: AlScN/GaN heterostructures are worth investigating due to the remarkable high gradients in spontaneous polarization at their interfaces, which brings them into play for a wide field of potential high-power and high-frequency electronic applications. In this work, AlScN/GaN heterostructures for high electron mobility transistor (HEMT) structures were grown by metalorganic chemical vapor deposition. We have investigated the impact of growth parameters on thick AlScN layers and on thin AlScN/GaN heterostructures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…The barrier and interlayer thicknesses measured by HRXRD increased with the temperature from 9.5 nm at 900 °C to 15.4 nm at 1200 °C (samples D2 and F2 grown on Al 2 O 3 , Table 1). The higher the deposition temperature, the more Sc gets incorporated into the layer, 22 even though the Sc flow was adjusted accordingly. We measured a Sc content of 1.4% in the sample grown at 900 °C and 9.0% in the one grown at 1200 °C.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The barrier and interlayer thicknesses measured by HRXRD increased with the temperature from 9.5 nm at 900 °C to 15.4 nm at 1200 °C (samples D2 and F2 grown on Al 2 O 3 , Table 1). The higher the deposition temperature, the more Sc gets incorporated into the layer, 22 even though the Sc flow was adjusted accordingly. We measured a Sc content of 1.4% in the sample grown at 900 °C and 9.0% in the one grown at 1200 °C.…”
Section: ■ Resultsmentioning
confidence: 99%
“…19 We demonstrated that the growth of AlScN by MOCVD is possible by employing a proprietary heating and gas mixing system which is tailored to the useage of Cp 3 Sc. 21 The effects of growth parameters such as temperature, growth mode, V/III ratio, and pressure were investigated, 22 as well as the diffusion behavior of Al-, Sc-, and Ga-atoms and the influence of GaN and SiN x cap layers on the oxidation of the underlying barrier. 23 SiN x was found to be the ideal passivation layer to prevent oxidation of the AlScN barrier while GaN tends to grow in a 3D-mode on Sc-rich layers.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-crystal Al 1−x Sc x N can be grown by molecular beam epitaxy (MBE) [ 9 ] on 100 mm wafers [ 37 ] with scandium concentration x from 0.06 to 0.36 [ 38 ]. The growth of Sc alloyed AlN via metal–organic chemical vapor deposition (MOCVD) had suffered from the lack of Sc precursors [ 39 ]; however, research in this field is catching up quickly, and the ability to grow 36% Sc alloyed Al 1−x Sc x N films on 100 mm wafers has been demonstrated [ 40 , 41 ]. High-quality polycrystalline Al 1−x Sc x N films can be deposited with physical vapor deposition (PVD) methods such as magnetron sputtering.…”
Section: Methodsmentioning
confidence: 99%
“…The epitaxial integration of wurtzite ScAlN on GaN was demonstrated recently with molecular beam epitaxy (MBE) and metal–organic chemical vapor deposition, , indicating the ability to produce a higher quality thin film material when compared with traditional sputtering techniques. One key area to exploit the high inherent polarization of ScAlN is in the design of next-generation III–N HEMTs, where ScAlN has been used as a barrier layer to increase channel charge densities by a factor of 5 higher than AlGaN-barrier GaN HEMTs. ,, …”
Section: Introductionmentioning
confidence: 99%